Characterization of upgraded fast pyrolysis oak oil distillate fractions from sulfided and non-sulfided catalytic hydrotreating. (15th August 2017) - Olarte, Mariefel V.; Padmaperuma, Asanga B.; Ferrell, Jack R.; Christensen, Earl D.; Hallen, Richard T.; Lucke, Richard B.; Burton, Sarah D.; Lemmon, Teresa L.; Swita, Marie S.; Fioroni, Gina; Elliott, Douglas C.; Drennan, Corinne
Highlights: Comprehensive analysis of catalytically upgraded oak bio-oil. Comparison between low oxygen content (LOC) and medium oxygen content (MOC) oils composition. Sulfur distribution in the different oil fractions from sulfided and non-sulfided bio-oil derived upgraded oils. Abstract: Catalytic hydroprocessing of pyrolysis oils from biomass produces hydrocarbons that can be considered for liquid fuel production. This process requires removal of oxygen and cracking of the heavier molecular weight bio-oil constituents into smaller fragments at high temperatures and pressures under hydrogen. We present in this paper the characterization of a group of five distillate fractions from each of two types of hydroprocessed oils from oak pyrolysis oil: a low oxygen content (LOC, 1.8% O, wet basis) oil and a medium oxygen content (MOC, 6.4% O, wet basis) oil. The LOC oil was generated using a sulfided hydrotreating system consisting of RuS/C and xMoS/Al2 O3 while the MOC was produced using non-sulfided catalysts, Ru/C and Pd/C. Elemental analysis and 13 C NMR (nuclear magnetic resonance) results suggest that the distillate fractions from both oils become more aromatic/unsaturated as they become heavier. Carbonyl and carboxylic groups were found in the MOC light fractions, while phenols were present in the heavier fractions for both MOC and LOC. Paraffin, iso-paraffin, olefin, naphthene, aromatic (PIONA) analysis of the light LOC fraction shows a predominance of paraffins with a minor amount of olefins. Sulfur analysis showed the comparative concentration of sulfur in the different fractions as well as the surprising similarity in content in some sulfided and non-sulfided fractions. These results can be used to direct future research on refinery integration and production of value-added product from specific upgraded oil streams.